Cervicovaginal levels of human beta defensins during bacterial vaginosis - Noda-Nicolau, Nathalia Mayumi [UNESP]; de Castro Silva, Mariana [UNESP]; Bento, Giovana Fernanda Cosi [UNESP]; Ferreira, Jeniffer Sena Baptista [UNESP]; Novak, Juliano [UNESP]; Morales, Júlia Andrade Pessoa [UNESP]; Tronco, Júlia Abbade [UNESP]; Bolpetti, Aline Nascimento [UNESP]; Pinto, Gabriel Vitor Silva [UNESP]; Polettini, Jossimara; Marconi, Camila [UNESP]; da Silva, Márcia Guimarães [UNESP] (Public Library of Science (PLoS), 2021)
Aims To compare the cervicovaginal levels of human beta defensin (hBD)-1, 2 and 3 of women according to the status of Nugent-defined bacterial vaginosis (BV). Methods A total of 634 women of reproductive age were included in the study. Participants were equally distributed in two groups: according to the classification of vaginal smears according to Nugent criteria in normal (scores 0 to 3) and BV (scores ≥7). Cervicovaginal fluid samples were used for measurements of hBDs1, 2 and 3 levels by enzyme-linked immunosorbent assay (ELISA). Levels of each hBD were compared between the two study groups using Mann-Whitney test, with p-value <0.05 considered as significant. Odds ratio (OR) and 95% confidence interval (95% CI) were calculated for sociodemographic variables and hBD1-3 levels associated with BV a multivariable analysis. Correlation between Nugent score and measured levels of hBDs1-3 were calculated using Spearman’s test. Results Cervicovaginal fluids from women with BV showed lower levels of hBD-1 [median 2,400.00 pg/mL (0–27,800.00); p<0.0001], hBD-2 [5,600.00 pg/mL (0–45,800.00); p<0.0001] and hBD-3 [1,600.00 pg/mL (0–81,700.00); p = 0.012] when compared to optimal microbiota [hBD-1: [median 3,400.00 pg/mL (0–35,600.00), hBD-2: 12,300.00 pg/mL (0–95,300.00) and hBD-3: 3,000.00 pg/mL (0–64,300.00), respectively]. Multivariable analysis showed that lower levels of hBD-1 (OR: 2.05; 95% CI: 1.46–2.87), hBD-2 (OR: 1.85; 95% CI: 1.32–2.60) and hBD-3 (OR: 1.90; 95% CI: 1.37–2.64) were independently associated BV. Significant negative correlations were observed between Nugent scores and cervicovaginal levels of hBD-1 (Spearman’s rho = -0.2118; p = 0.0001) and hBD-2 (*Spearman’s rho = -0.2117; p = 0.0001). Conclusions Bacterial vaginosis is associated with lower cervicovaginal levels of hBDs1-3 in reproductive-aged women.